Simulation of Fermentation Pathway Using Bees Algorithm - Leong, Yi Ying; Chong, Chuii Khim; Chai, Lian En; Deris, Safaai; Illias, Rosli; Omatu, Sigeru; Mohamad, Mohd Saberi (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false EN-US JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> <!–StartFragment–> In this paper, we propose Bees Algorithm (BA) to enhance the performance in estimating the parameters for metabolic pathway data to simulate fermentation pathway for Saccharomyces cerevisiae. However, the parameter estimation of biological processes has always been a challenging task due to the complexity and nonlinear equations. Therefore, we present this algorithm as a new approach for parameter estimation for biological interactions to obtain more accurate parameter values. The result shows that BA outperforms other estimation algorithms as it produces the most accurate kinetic parameters, which contributes to the precision of simulated kinetic model. <!–EndFragment–>